Enhanced renal ischemia/reperfusion injury repair potential of exosomes derived from B7-H1high mesenchymal stem cells - He, Jiahui; Yao, Yawei; Wang, Ruiyan; Liu, Yujia; Wan, Xingyu; Wang, Hao; Zhou, Yuqiang; Wang, Wenjing; Ma, Yan; Lv, Xinghua (Frontiers in Genetics, 2025)
Two subgroups with high expression of B7-H1 and low expression of B7-H1 were successfully isolated from primitive human umbilical cord mesenchymal stem cells. And exosomes with high B7-H1 expression and low B7-H1 expression were successfully isolated. In comparison to the sham-operated group, mice in the IRI group demonstrated elevated serum levels of blood urea nitrogen (BUN) and serum creatinine (Scr), accompanied by a more pronounced degree of renal tissue damage. The administration of exosomes via the tail vein markedly accelerated the recovery of renal function in IRI mice, with the therapeutic effect beingmore pronounced in those treated with B7-H1high-Exo. Moreover RNA sequencing of mouse kidney treated with B7-H1high-Exo and B7-H1low-Exo showed that eight genes (C3, IRF7, AREG, CXCL10, Aldh1l2, Fnip2, Vcam1, St6galnac3) were involved in the pathophysiological process of ischemia-reperfusion injury. The in vitro and in vivo experiments showed that the expression level of C3 protein was significantly decreased, which indicated that B7-H1high-Exo played a therapeutic role by down-regulating C3.